Evaluation of the Efficacy of Entecavir and Tenofovir in the Treatment of Chronic Hepatitis B: A Retrospective Study - Senol, Arzu; Ozer Balin, Safak (Bilimsel Tip Yayinevi, 2019)
Introduction: Chronic hepatitis B is one of the most important causes of morbidity and mortality associated with liver disease. The aim of this study was to retrospectively compare tenofovir and entecavir patients in terms of side effects and biochemical and virological response for 3 years. Materials and Methods: Between January 2013-December 2016, 118 patients who were at least at the age of 18 years and who had HBsAg positivity for at least 6 months were evaluated. Liver enzymes, HBV-DNA, alpha fetoprotein, hepatitis B surface antigen (HBsAg), hepatitis B early antigen (HBeAg), hepatitis B surface antibody (anti-HBs) and liver biopsy results were recorded during follow-up period (3., 6.,12., 24., 36. months). Data analysis was performed using SPSS-22 software pack. A p value of less than 0.05 was considered statistically significant. Results: Seventy (59.3%) of the patients were treated with tenofovir and 48 (40.6%) with entecavir. HBV-DNA negativity rates were found to be higher than HBeAg positivity in HBeAg negative cases. HBV-DNA negative rates were higher in the tenofovir group compared to the entecavir group. However, these rates were not statistically significant. There was no significant difference in ALT normalization rates between the tenofovir group and entecavir group. HBeAg seroconversion was detected in 3 cases and HBsAg loss in 2 cases in the tenofovir group. HBeAg seroconversion developed in 1 case and no HBsAg loss was observed in the entecavir group. Conclusion: According to the data obtained from our study, no significant difference was found between tenofovir and entecavir monotherapy in both HBeAg positive and HBeAg negative chronic hepatitis B cases, in suppressing HBV-DNA replication and maintaining virological response. Both appear to be effective, safe and well tolerated treatment options.
Keywords: Chronic Hepatitis B; Tenofovir; Entecavir